Pengujian pada Regresi Ridge dan Penerapannya terhadap Data Produk Domestik Regional Bruto Provinsi Jawa Barat - Weni Nuryati; Suliadi Suliadi (UNISBA Press, 2023)
Abstract. Ridge regression is one of the methods used to stabilize the value of the regression coefficient caused by multicollinearity. In ridge regression, to reduce the impact of multicollinearity is carried out by adding ridge parameter c to the hat matrix. This ridge parameter makes the regression coefficients have a smaller variance than the least squares method estimator variance. However, the ridge estimates are biased. Thus, hypothesis testing using the usual method cannot be applied to the coefficients ridge regression. Therefore Bae, et al., (2014) developed a method for testing the hypothesis of the coefficients of ridge regression. This thesis aims to apply this method to the gross regional domestic product data for West Java province in 2022. Based on the results of the research, it shows that there is a multicollinearity problem in the data, so it is modelLed using ridge regression. it was obtained The ridge regression model : . From the results of testing the hypothesis, it can be concluded that the independent variables, namely local original income (X1), general allocation funds (X2), profit sharing funds (X3), regional expenditures (X4) and labor (X5) together have a significant effect on the PDRB (Y) of West Java Province in 2022. The ridge regression model is returned to the original model . Abstract. Ridge regression is one of the methods used to stabilize the value of the regression coefficient caused by multicollinearity. In ridge regression, to reduce the impact of multicollinearity is carried out by adding ridge parameter c to the hat matrix. This ridge parameter makes the regression coefficients have a smaller variance than the least squares method estimator variance. However, the ridge estimates are biased. Thus, hypothesis testing using the usual method cannot be applied to the coefficients ridge regression. Therefore Bae, et al., (2014) developed a method for testing the hypothesis of the coefficients of ridge regression. This thesis aims to apply this method to the gross regional domestic product data for West Java province in 2022. Based on the results of the research, it shows that there is a multicollinearity problem in the data, so it is modelLed using ridge regression. it was obtained The ridge regression model : . From the results of testing the hypothesis, it can be concluded that the independent variables, namely local original income (X1), general allocation funds (X2), profit sharing funds (X3), regional expenditures (X4) and labor (X5) together have a significant effect on the PDRB (Y) of West Java Province in 2022. The ridge regression model is returned to the original model .